1997
DOI: 10.1017/s0007485300037184
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and weather factors influencing the annual flight cycle of Prostephanus truncatus (Coleoptera: Bostrichidae) and its predator Teretriosoma nigrescens (Coleoptera: Histeridae) in Benin

Abstract: Investigations were carried out in southern Benin on the annual flight cycle and the effects of weather variables on the flight activity of Prostephanus truncatus (Horn) and its natural enemy, Teretriosoma nigrescens Lewis. Two seasonal peaks in flight activity of P. truncatus were observed, one between the end of December and the beginning of January and a second one between May and June. Teretriosoma nigrescens showed a single delayed peak in June, approximately six weeks after the major peak of P. truncatus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
2
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 10 publications
2
22
2
1
Order By: Relevance
“…Similar peaks in catch have been reported previously from Mono province in Benin (Borgemeister et al, 1997b) but not from the coastal zone where there is a single annual rise and fall, presumably because humidities there do not drop below 50% during the period of the Harmattan. In the case of the Benin coastal zone, P. truncatus trap catch was related only to mean temperature (Borgemeister et al, 1997b;Scholz et al, 1998), a finding consistent with the current study in years when humidity is not limiting. The observed response of the beetle to low humidity conditions confirms previous reports.…”
Section: Discussionsupporting
confidence: 87%
“…Similar peaks in catch have been reported previously from Mono province in Benin (Borgemeister et al, 1997b) but not from the coastal zone where there is a single annual rise and fall, presumably because humidities there do not drop below 50% during the period of the Harmattan. In the case of the Benin coastal zone, P. truncatus trap catch was related only to mean temperature (Borgemeister et al, 1997b;Scholz et al, 1998), a finding consistent with the current study in years when humidity is not limiting. The observed response of the beetle to low humidity conditions confirms previous reports.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, the temperature sums during the development period did not influence the size of the final progeny densities, and indirectly also not the number of flyers, it can be assumed that higher temperatures promoted dispersal, possibly due to the increased activity of the insects (Johnson, 1969). During a three-year observation period near the IITA Benin station, Borgemeister et al (1997) found mean temperature to be the only meteorological variable to influence the fluctuations in flight activity, recorded with pheromone-baited traps. It can be assumed that trap catches in our experiment were not affected by increased pheromone release rates under warmer conditions, as (i) higher mean temperatures also increased migration in our experiment on flight initiation, and (ii) accompanying trap catches of the predator Teretriosoma nigrescens Lewis (Coleoptera: Histeridae) in the experiment of were not influenced by temperature.…”
Section: Discussionmentioning
confidence: 98%
“…Obeng-Ofori & Coaker, *Fax: 49511 762 3015 E-mail: scholz@mbox.ipp.uni-hannover.de 1990). The two main components of the pheromone have been identified (Cork et al, 1991), synthesized, and used to determine the beetle's spread and flight activity (Richter & Biliwa, 1991;Borgemeister et al, 1997). Studies in Kenya (Giles et al, 1995;Nang'ayo, 1996), Benin and Mexico (Tigar et al, 1994) showed strong seasonal fluctuations in the numbers of P. truncatus caught with pheromone-baited traps.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Successful movement between areas of suitable habitat is essential for their survival and reproduction, and impacts the spatiotemporal dynamics of the species (Ronce 2007, Walter & Hengeveld, 2014. Naturally, ecological studies have found significant variation in the movement of organisms of particular species and in the factors driving this variation (Borgemeister et al 1997, Edde et al 2006. Understanding the underlying basis of this movement has proved elusive.…”
Section: Initiating Emigration and Influencing Resource Locationenvirmentioning
confidence: 99%